Phrasing and relative clauses in Chimwiini - Kisseberth, Charles W. (ZAS Papers in Linguistics, 2010)
We focus in this paper on two prosodic phenomena in Chimwiini: vowel length and accent (or High tone). Vowel length is determined in part by a lexical distinction between long and short vowels, and also by various morphophonemic processes that derive long vowels. Accent is penult in the default case, but final under certain morphosyntactic conditions. In order to account for the distribution of vowel length and the location of accents in a Chimwiini sentence, it is necessary to segment sentences into a sequence of phonological phrases. This paper examines the phonological phrasing of both canonical relative clauses and what we refer to as "pseudo-relative" clauses. An account of relative clause phrasing is of critical importance in Chimwiini due to the extensive use of pseudo-relatives in the language. Close examination of the pseudo-relatives reveals that their phrasing is not exactly the same as the phrasing of canonical relative clauses.